2019
DOI: 10.5114/pjr.2019.92422
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound elastography as a potential method to evaluate entrapment neuropathies in elite athletes: a mini-review

Abstract: Entrapment neuropathies constitute a significant albeit still neglected problem in athletes. Currently available diagnostic options in patients with suspected neuropathies, nerve conduction studies, and magnetic resonance imaging have some drawbacks, mostly related to their invasive character, high cost, and limited availability. This paper reviews published articles documenting the use of ultrasound elastography, a novel technique to determine tissue strain, in the evaluation of nerve stiffness in entrapment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…In addition to shorter acquisition time and less discomfort, advantages of ultrasound include wide availability, cheap price, and non-invasive nature. [ 1 3 ] Conventional ultrasound can quantify cross sectional area (CSA) of the peripheral nerves and can also detect some morphological changes like alteration in the nerve echogenicity. [ 1 , 4 ] Conventional ultrasound was reported to be of great benefit in the diagnosis of different acquired and hereditary neuropathies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to shorter acquisition time and less discomfort, advantages of ultrasound include wide availability, cheap price, and non-invasive nature. [ 1 3 ] Conventional ultrasound can quantify cross sectional area (CSA) of the peripheral nerves and can also detect some morphological changes like alteration in the nerve echogenicity. [ 1 , 4 ] Conventional ultrasound was reported to be of great benefit in the diagnosis of different acquired and hereditary neuropathies.…”
Section: Introductionmentioning
confidence: 99%
“…[13] Several important peripheral nerves were studied by elastography like the median, sciatic, and tibial nerves, in normal subjects and in cases of peripheral neuropathy. [15][16][17][18][19][20][21][22][23][24][25] The aim of this work is to study the sonoelastographic features of the common fibular nerve in healthy adult subjects.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the elasticity of nerve was also an important parameter to evaluate entrapment neuropathies. A systemic review revealed the median nerve became stiffer after compression under shear wave elastography quantification [ 7 , 8 ]. Shear wave elastography had high sensitivity to detect changes in median nerve elasticity [ 9 ].…”
Section: Introductionmentioning
confidence: 99%